Managing disaster preparedness for institution of higher learning: A study in Perlis - Jusoh, Muhammad Shahar; Bahari, Azuddin; Md. Isa, Evawaynie Valquis (2007)
Unprecedented floods disaster that hit Johore, Pahang, Terengganu and Kelantan was due to abnormal weather conditions. Heavy rain which fall continuously non stop for between 3 to 4 days has raised the water level in some areas to a height of 15 feet deep. The flood disasters have caused devastating loss of property and life and some 100,000 people were evacuated to flood relief centers. Some of the floods victim lost all their belonging and property. Flood disaster has also caused water borne diseases to prevail. The future is bleak for these flood victims. Continuous government assistance is needed for these flood victims who lost everything is needed. Year in and year out, the monsoon season have cause floods disaster especially in the east coast state and is now a yearly common phenomena. However, the level of awareness and preparedness among the Malaysian community and the government machinery is still questionably low. Presently, there are 18 public universities in the country, the issue is what is the level of awareness does students and staff of the university put on the issue of floods or other natural disaster? Do we at the University are ready to face disaster situations if it occur in the University? At this juncture, the experiences of UniMAP’s contribution to the University’s community, the local community vis-à-vis the Malaysian Mechanism Disaster Management and functioning alongside the state machinery of Perlis state government during 17 December 2005 flood disaster can be used as an example. The aim of this study is to examine the disaster preparedness in University and to propagate the importance of disaster preparedness among the students and staffs through education. This pilot project will be conducted through interviews, observations and surveys. It is expected that this study will shed some light for further effective implementation of disaster preparedness management.